PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA MONTIGO RESORT NONGSA BATAM - Yosua Parhorasan Manullang; Jovani Horianto (Adisam Publisher, 2024)
This study aims to analyze the impact of leadership styles on employee performance at Montigo Resort Nongsa Batam. The study uses a quantitative method and surveys 30 employees to measure the influence of transformational, transactional, and laissez-faire leadership styles on employee performance. The results of the simple linear regression analysis show that transformational leadership style has a significant positive impact, whereas the transactional leadership style does not significantly affect employee performance. These findings emphasize the importance of transformational leadership in enhancing employee performance at Montigo Resort Nongsa Batam.